Age-Dependent Abiotic Stress Resilience in Plants. (July 2021) - Rankenberg, Tom; Geldhof, Batist; van Veen, Hans; Holsteens, Kristof; Van de Poel, Bram; Sasidharan, Rashmi
Abstract : Developmental age is a strong determinant of stress responses in plants. Differential susceptibility to various environmental stresses is widely observed at both the organ and whole-plant level. While it is clear that age determines stress susceptibility, the causes, regulatory mechanisms, and functions are only now beginning to emerge. Compared with concepts on age-related biotic stress resilience, advancements in the abiotic stress field are relatively limited. In this review, we focus on current knowledge of ontogenic resistance to abiotic stresses, highlighting examples at the organ (leaf) and plant level, preceded by an overview of the relevant concepts in plant aging. We also discuss age-related abiotic stress resilience mechanisms, speculate on their functional relevance, and outline outstanding questions. Highlights: The processes of aging, such as leaf development, senescence, and phase transitions from juvenile to adult plants, are genetically programmed and highly controlled by complex regulatory pathways. During aging, plants alter their organ morphology, sink–source balances, and chemical composition, including changes in redox status and hormone levels, which will collectively determine how abiotic stress signals are perceived and processed. The actual abiotic stress resilience of a plant organ (e.g., a leaf) is determined by the complex integration of age-related developmental factors and stress response pathways. Age-related abiotic stress resilience manifests by differential responses with respect to (i) morphological plasticity to allow stress escape or endurance; (ii) an altered tolerance toward photoinhibition and reactive oxygen species (ROS) build-up preventing oxidative damage; and (iii) a changing sensitivity toward induced senescence to facilitate resource allocation and stress survival.